Bredigite bioceramic-based barrier membrane promotes guided bone regeneration by orchestrating an immuno-modulatory and osteogenic microenvironment - Hu, Longwei; Zhu, Yun; Guo, Yibo; Zhang, Chenping; Wang, Yang; Zhang, Zhen (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
Schematic 1. Illustration of proposed mechanisms by which bredigite-containing scaffolds provide a dynamic immuno-modulatory and repair-supportive microenvironment for guided bone regeneration. [Display omitted] •BRT-containing scaffold as a potential GBR barrier membrane.•scRNA-seq revealing responses of BMSCs to BRT.•Osteo-immunomodulatory property of BRT-containing scaffolds in GBR. Barrier membranes play an important role in guided bone regeneration (GBR) and have been primarily considered as physical barriers. Due to their inherent “foreign body” properties, barrier membranes introduced during GBR procedures unavoidably modify the local immune microenvironment, with consequent impacts on osteogenesis. In bone tissue engineering applications, inorganic bioceramics have been shown to possess the abilities to modulate the local immune response and promote the differentiation of stem cells along osteogenic lineages. Moreover, these bioceramics can be easily incorporated into scaffold membranes, thus demonstrating significant potential as a barrier membrane material for GBR. Herein, an inorganic bredigite (BRT, Ca7MgSi4O16) bioceramic-containing scaffold was fabricated and characterized, and its effects on the immune response and osteogenesis during GBR were investigated. The results indicated that the BRT-containing scaffolds promoted the migration and osteogenic differentiation of bone marrow-derived stem cells (BMSCs). Single-cell RNA sequencing analysis indicated a unique microenvironment and subpopulation of BMSCs cultured on the BRT scaffolds, which exhibited increased osteo/chondrogenic and angiogenic differentiation potential. Furthermore, the BRT-containing scaffolds induced macrophage polarization into the pro-regenerative M2 phenotype, which subsequently promoted the migration and osteogenic differentiation of BMSCs. Additionally, in an in vivo rat model, the BRT-containing membrane was confirmed to enhance the immune microenvironment and support bone regeneration in a cranial critical-size defect. Collectively, these findings indicate that the BRT-containing scaffold membrane possesses dual immunomodulatory and osteogenic properties, offering a potentially beneficial GBR membrane for clinical application.